Three-dimensional finite element analysis of the stress distribution pattern in the design modifications of U-shaped palatal major connector - Ramakrishnan Hariharan; Singh Raj (Wolters Kluwer Medknow Publications, 2010)
Background: The U-shaped maxillary major connector is considered to be the least-desirable design by many prosthodontists as it lacks rigidity, which is a primary requisite for a major connector. Aims and Objectives: Design modifications in the U-shaped palatal major connector are desired because it lacks rigidity. The study also aimed to determine the best design when a U-shaped palatal major connector is indicated for clinical use. Materials and Methods: The normal design and the design-modified models (modification 1, 2, 3, 4) were loaded at the functional cusps of the premolars and the molars with a magnitude of 200 N, 250 N and 300 N at angulations of 60 o and 90 o on both sides of the maxillary arch. Results for each loading were obtained as stress distribution colored images and numerical values were recorded. A three-dimensional finite element analysis study of the design-modified models was performed using two finite element softwares, namely PRO-E and IDEAS. Results: The least stress value of 7.86 Megapascals (MPa) at 200 N, 60 o was recorded for the double-thickness design, followed by design 1, which was 8.03 MPa. The least stress value for the palatal mucosa and ligament was provided by design modification 1 (0.5 mm-thick U-shaped connector, 9 mm anteroposteiorly, 14.6 mm laterally), which was 9.78 MPa and 2.98 MPa, respectively. Conclusion: The double-thickness group exhibited the least internal stress for the U-shaped major connector. However, it delivered the greatest stress to the palatal mucosa and the periodontal ligaments.